Direct Technology Diffusion in Higher Education: Evidence from Doctoral Students - Atul Kumar; Jaiprakash Paliwal; Mahesh Singh; Vishwas Pendse; Amandeep Saini; Rajesh Gade; Rahul Dhaigude; Abhay Bora; Sagar Nimbalkar; Shirish Raibagkar (ASEAN Journal of Educational Research and Technology, 2027)
This study compares direct and indirect technology diffusion in higher education, focusing on plagiarism detection software in Indian doctoral education. Using a quantitative survey of research scholars, the study finds that direct diffusion significantly improves outcomes. Similarity levels decreased substantially under direct diffusion, indicating more accurate application of plagiarism rules. Additionally, direct diffusion reduced the time required and lowered costs considerably. The findings suggest that direct access empowers users, minimizes intermediary-related inefficiencies, and enhances both effectiveness and efficiency. The study highlights cost-effectiveness as a key enabler and recommends that policymakers and institutions promote direct technology diffusion to improve adoption and strengthen academic integrity in higher education.